Production and characterization of partially purified thermostable alkaline protease by Bacillus subtilis SFL for blood destaining and dehairing applications - Elkafass, Eetmad N.; Ghaly, Mohamed F.; El-Sayed, El-Sayed A.; Abdel-Haliem, Mahmoud E.F. (Journal of Advanced Veterinary Research, 2024)
Microbial proteases have been preferred over animal and plant proteases because of their basic properties and ease of production. Bacillus subtilis SFL, an alkaline-thermal protease-producing bacterium was isolated from different sources of wastewater and identified using morphological, biochemical, and molecular methods. The 16S rDNA sequence has been deposited in GenBank with accession number OP714187. Partial purification of alkaline protease was performed by precipitation by 60% ammonium sulfate and ethyl acetate by the ratio (1:1) and column chromatography (gel filtration) by using a sephadex G-100. The optimum temperature and pH of the partially purified alkaline-thermal protease of Bacillus subtilis SFL was at 40Â°C and pH 8.0. Our results show that 40 g/l of meat extract and 12 g/l of xylose serve as the best nitrogen and carbon sources respectively for the production of this enzyme. The effect of tested metal ions indicated that Mg+2, Ca+2, Na+, Fe+2, Cu+2, Co+2 and Cd+2 inhibited the activity of the protease from Bacillus subtilis SFL. The crude and partially purified protease from B. subtilis SFL substantially degraded red blood cells, distained blood color, dehaired cow skin and decomposed cow hair.